(untitled) (Orthodontic Journal of Nepal, 2022)
Introduction: Knowledge of the safe zone of mini-implant placement guides clinicians in choosing where to place mini-implants. Several studies evaluated the safe zone for mini-implants placement, but only a very few previous studies have taken different skeletal patterns into account when assessing measurements. Objective: The purpose of this cross-sectional, comparative study was to compare the inter-radicular distance and buccal cortical bone thickness in Class I and Class II skeletal malocclusion patterns. Materials and Methods: A total of 62 CBCT images of patients with Class I and Class II skeletal malocclusion were obtained from the records of the department of Oral medicine and Radiology, Kathmandu University Teaching Hospital. The inter-radicular distance and buccal cortical bone thickness were measured at four different heights (2, 4, 6 and 8 mm) from the CEJ towards the apex. These measurements were measured between different skeletal pattern and gender with independent t-test. The intergroup comparison at different height from CEJ was done with ANOVA followed by Tukey’s post-hoc test to see the difference within the category. Result: There was a statistically significant difference observed in the inter-radicular distance between the maxillary first and second premolars at a height of 6 mm between Class I and Class II malocclusion patterns (p = 0.03). There were differences observed in the inter-radicular distance of the mandible at a different height based on skeletal malocclusion pattern, which was not statistically significant (p > 0.05). The buccal cortical bone thickness between the maxillary central and lateral incisors at the height of 2 mm from CEJ between Class I and Class II skeletal malocclusion patterns was statistically significant (p = 0.01). The buccal cortical bone thickness of the mandible at different heights based on skeletal malocclusion pattern there were differences observed which were not statistically significant (p > 0.05). Conclusion: The inter-radicular distance and buccal cortical bone thickness could be influenced by different skeletal patterns and tend to increase from the CEJ to the apex in both Class I and Class II skeletal patterns.